Hydrogen as an Energy Vector: Analysis of the Global Development on Decision-Making Support Systems - Espinoza-Perez, A; Santander-Tapia, P; Velastin-Osorio, N (Springer Science and Business Media Deutschland GmbH, 2025)
Today, the implementation of energy systems based on renewable energies is proposed as one of the different measures to address climate change. However, in this context, investments in the security and robustness of these systems are crucial. Among renewable energy sources, hydrogen production has emerged as an environmentally friendly energy solution for addressing climate change. However, regarding the systematic literature review presented in this research, there are still several research challenges in decision-making for designing a hydrogen supply chain. No study has assessed the hydrogen supply chain with all its stages from a sustainable perspective. Furthermore, despite their potential, a significant challenge is developing hydrogen in Africa and Latin America. © The Author(s), under exclusive license to Springer Nature Switzerland AG 2025.